Pengaruh Brand Awareness, Brand Image, dan Harga terhadap Loyalitas Merek pada Mahasiswa Pengguna Smartphone - Zalkha Soraya; A. Ade Wahyudi Asdar; Karmila Karmila; Della Puspita Sari; Wahyu Anugrah; Armayanti Armayanti; Ranti Ranti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of brand awareness, brand image, and price on brand loyalty in student smartphone users. The research background is based on increasing competition between smartphone brands which requires companies to understand the factors that drive consumer loyalty, especially among students who are known as active and critical users. This study uses an associative quantitative approach with a survey method of 82 respondents from the Management Study Program Class of 2022, Muhammadiyah University of Makassar. The results showed that brand awareness, brand image, and price partially and simultaneously had a significant effect on brand loyalty. The R² value of 0.825 indicates that the three independent variables explain 82.5% of the variation in brand loyalty. This finding confirms the importance of building a strong brand image, maintaining brand awareness, and setting prices in accordance with consumer value perceptions. This research provides strategic implications for companies in designing more effective marketing to retain customers in the student segment